Imaging Real-Time Tactile Interaction With Two-Person Dual-Coil fMRI - Renvall, Ville; Kauramäki, Jaakko; Malinen, Sanna; Hari, Riitta; Nummenmaa, Lauri (Frontiers in Psychiatry, 2020)
Studies of brain mechanisms supporting social interaction are demanding because real interaction only occurs when the persons are in contact. Instead, most brain imaging studies scan subjects individually. Here we present a proof-of-concept demonstration of a two-person blood oxygenation dependent (BOLD) imaging of brain activity from two individuals interacting inside the bore of a single MRI scanner. We developed a custom 16-channel (8 + 8 channels) two-helmet coil with two separate receiving elements providing whole-brain coverage, while bringing participants into a shared physical space and realistic face-to-face contact. Ten subject pairs were scanned with the setup. During the experiment, subjects took turns in tapping each other’s’ lip versus observing and feeling the taps timed by auditory instructions. Networks of sensorimotor brain areas were engaged alternatingly in the subjects during executing motor actions as well as observing and feeling them; these responses were clearly distinguishable from the auditory responses occurring similarly in both participants. Even though the signal-to-noise ratio of our coil system was compromised compared with standard 32-channel head coils, our results show that the two-person fMRI scanning is a feasible in studying the brain basis of social interaction.